2020
DOI: 10.1007/s00521-020-05365-w
|View full text |Cite
|
Sign up to set email alerts
|

Deep autoencoder for false positive reduction in handgun detection

Abstract: In an object detection system, the main objective during training is to maintain the detection and false positive rates under acceptable levels when the model is run over the test set. However, this typically translates into an unacceptable rate of false alarms when the system is deployed in a real surveillance scenario. To deal with this situation, which often leads to system shutdown, we propose to add a filter step to discard part of the new false positive detections that are typical of the new scenario. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Several works addressed reducing the number of FP and FN in handgun detection in realistic video surveillance environments using pre-processing [16,4] and post-processing approaches [26,19]. For example, the authors in [4] presented a pre-processing technique that help improving the quality of the videos in changing illumination environments.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works addressed reducing the number of FP and FN in handgun detection in realistic video surveillance environments using pre-processing [16,4] and post-processing approaches [26,19]. For example, the authors in [4] presented a pre-processing technique that help improving the quality of the videos in changing illumination environments.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that this technique improves the detection of knives in videos. The experimental results in [26] showed that analyzing the detected handguns using an auto-encoder improves the overall precision of the detection in videos. In [19], the authors showed that the use of binarization techniques such as OVO and OVA improves the overall performance of handguns and knives detection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this application, the closed-circuit television is widely used for recognizing dangerous situations, where the closed-circuit television is considered as the effective operational requirement in terms of safety aspects [1][2][3]. The main purpose of closed circuit television is to provide security, crime investigation, deterrence, and reduction in insurance costs [4,5]. However, the deterrence effects of closed circuit television cameras vary from the different time periods and crime categories.…”
Section: Introductionmentioning
confidence: 99%
“…Problems arise such as lack of personnel and overlooked threats, given that after 20 min of monitoring a CCTV system, operators fail to detect objects or activities [4,5]. This calls for innovation in automated systems, optionally combined with human attention, for the detection of violent actions [6][7][8] or gun detection [9][10][11]. Safety in all areas of daily life has always been a general concern over time and in all parts of the world.…”
Section: Introductionmentioning
confidence: 99%